Prosody in brazilian sign Language – a Corpus study of Enem-2017 - Silva, Rúbia Carla da (2021)
Facial joints reflect on prosodic subcomponents of oral and sign languages. Therefore, it is a research of an applied, documentary, of a descriptive-exploratory character, through the observational method. The objective is to understand which are the facial movements of intonational prosodic manifestation in Brazilian Sign Language and what it means in a narrative context. As a methodological procedure, we opted for a bibliographic review about American Sign Language (ASL) and Sign Language Israeli and the analysis of a question of the High School National Exam (ENEM) of 2017 – the first edition of the test in Brazilian Sign Language. As results, were created a table about elements of superior facial movements and their means, furthermore verify a relevant contribution to research for the linguistic legitimization of Brazilian Sign Language, for the analyses about teaching and learning sing languages, for the signification, comprehension, and production parlance. Consequently, emphasize a new look and research about the linguistic of Brazilian Sign Languages, due to the scarceness of this publication studies.